(3GdMeGjI GdLfGFjI aj ehGLgI LQGFe GdeQhQ (B: s (3OQGSI ebGQfI (B/ s - (3JGeQ SYO QRb YHOgs; (3YeQ eMeO eMeO SGdes; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2020)
(3CUHMJ GdSjGSg GdLfGFjg GdeJHYg dehGLgg GdLQGFe hGdeTcdGJ hGdGReGJ GdeQhQjI eTcdI YGdejI JYGfj efgG GdeLJeYGJ GdeYGUQI(B. (3abO HQRJ eTcdI GdeQhQ fJjLI dJYGXe MLe MQcI Gdfbd Ydi GdWQb fXkQG dJRGjO eYOd edcjI GdSjGQGJ GdNGUI cPG ddGQJaGY GdeSJeQ aj YOO GdQMdGJ GdJj jbhe HgG GdTNU, heJhSW Whd GdQMdI ShGA CcGfJ QMdGJ ddYed Ch ddJQajg, aef GdeYdhe Cf gfGc JVNkeG eJSGQYG aj MLe hGeJOGO GdJLeYGJ GdScfjI GdQFjSjI, ceG Cfg cdeG GQJaY ONd GdaQO JHGYO ecGfG GdYed hGdScf, gPG HGdEVGaI dJVNe MLe GdeTQhYGJ, hbO COi gPG Edi JVGYa MLe MQcI Gdfbd HeNJda hSGFdg, NGUI Gdfbd GdHQj Ydi GdWQb, hgh eG jJWdH hLhO JfXje Ydej eJWhQ hSjGSI LfGFjI hGVMI ai ehGLgg LQGFe GdeQhQ ddMO ef MhGOK GdeQhQ GdJj JYO ef Cge CSHGH GdhajGJ aj eNJda GdeLJeYGJ, hCUHM JfXje GdeQhQ ef GdbVGjG GdbhejI eJYGXeI GdCgejI; MjK Ef dgG GfYcGSGJ eHGTQI Ydi GdMjGI GdGbJUGOjI hGdGLJeGYjI hGdKbGajI hGdSjGSjIs
2023 (3GWQhMI(B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGF(B0s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFis; (3bGfhf GdeQhQs; (3GdeSFhdjI GdLfGFjIs; (3GdLfM GdeQhQjIs; (3GdeSDhdjI GdLfGFjIs; (3GdLRGAGJ aj bGfhf GdeQhQs; (3GdbGfhf GdeQhQj GdeUQjs; (3GdbGfhf GdeQhQj GdaQfSjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFj s